Longfang - Robson, Mark, 1966- (London : Simon and Schuster, 2009)
Kira and her dusk dragon, Longfang, set out with three other Dragonriders to find the third orb needed to save the Oracle.
6.5
3-6
3-6
Keywords: Dragons -- Juvenile fiction; Dragons -- Fiction; Fantasy; Dragons -- Fiction; Fantastic fiction; Fantastic fiction